Factors Affecting Survival of Pregnant Women with COVID-19 and Our First Extracorporeal Membrane Oxygenation Results - Selda Tekin; Esra Adıyeke; Elif Erdoğan Öngel; Nurten Bakan (Türk Yoğun Bakim Derneği Dergisi)
Objective: The purposes of our study were to determine the relationship between coronavirus disease (COVID) pneumonia and mortality and immunization status of patients and to present our first extracorporeal membrane oxygenation (ECMO) experiences by retrospectively evaluating pregnant women. Materials and Methods: The research was conducted by screening the files of 37 pregnant/postpartum COVID-2019 cases monitored and treated in the intensive care unit between March 1, 2020 and December 1, 2021. The patients’ ages, systemic comorbidities, vaccination details, and clinical and laboratory features were recorded and analyzed. The patients were divided into two groups as survivors (group 1; n=17) and exitus ones (group 2; n=20); and the results were compared statistically. Results: Of 37 patients, 17 (45.9%) survived (group 1) and 20 (54.1%) died (group 2) with a median of 31 gestational weeks and 9 days length of stay in the ICU. ICU admission time [which day of polymerase chain reaction (PCR)+] and cesarean time (which day of PCR+) were 8 days. Nine (24%) patients received ECMO and mechanical ventilation, with 6 (66.6%) exitus and 3 (33.3%) survivors who were discharged from the hospital without sequelae. Of 37 pregnant/postpartum patients, 36 were unvaccinated. Conclusion: Vaccination should be given priority in pregnant women, and ECMO may be effective in the recovery of oxygenation in pregnant COVID-19 patients.